Consulta do Conselho Ultramarino a D. João IV, rei de Portugal sobre a nomeação de embaixadores para o Japão e apresenta em 1º lugar Gonçalo de Sequeira de Sousa (1643)
This archival transcription comprises a 17th-century Portuguese colonial administrative dossier, dated 9–24 December 1643, originating from Macau and preserved in the Arquivo Histórico Ultramarino (AHU). It documents a formal consultation of the Overseas Council concerning the dispatch of a royal embassy to the Shogun of Japan, authorised by the Portuguese Crown—most likely Dom João IV following the Restoration of 1640—and countersigned by officials including Jorge de Alasquirque, João de Lindo Figueiro, Joana Roiz, and António de Albuquerque. The dossier details the Council’s recommendation to redirect two vessels originally destined for China to Macau; the nomination of envoys—including Gonçalo de Sequeira de Sousa, Teodósio de Oliveira, Veyra Leite, Zorzi, Francisco Barroso, and Gomes Luís de Souza—as ambassadors; elaborate protocols for diplomatic correspondence, ceremonial gifts (including gilded parchment letters, gold-silk coverings, coral beads, armour, and a copper-portrait diptych), and expenditure allocations totalling one thousand cruzados and five hundred tostões; logistical arrangements for personnel, including secretary, chaplain, and attendants; and financial provisions drawn from Macau’s municipal treasury (*cofradia*) and local villages such as Tinha. Central themes include the strategic reassertion of Portuguese sovereignty post-Iberian Union, the restoration of trade with Japan following the 1639 expulsion, the diplomatic primacy of direct royal accreditation over viceregal dispatch, and the institutional autonomy of Macau’s *Senado da Câmara*. The material is essential for research on early modern Iberian diplomacy, Luso-Japanese relations, colonial administration in maritime Asia, and the political economy of the Estado da Índia.
Keywords: Archival Provenance Lisbon Goa Madrid; Council of State Proceedings; Estado da Índia archives; Goa administrative documentation; Gonçalo de Sousa; Henrique da Conceição; Luso-Asian history; Luís de Sousa; Macau Diplomatic Records; Macau–Nagasaki Trade Route; Malacca jurisdiction; Portuguese Colonial Administration; Portuguese India administration; Portuguese colonial trade regulation; Transcription; colonial petition; cross-cultural commercial practice; fiscal oversight; requерimento; unlicensed maritime commerce